Isolation, Purification, and Characterization of Antimicrobial Substances from Endophytic Actinomycetes - Sunaryanto, Rofiq; Mahsunah, Anis Herliyani (UI Scholars Hub, 2013)
Antimicrobial active substances produced by endophytic actinomycetes were isolated and purified. Plant samples were obtained from four different medicinal plants namely Curcuma domestica, Phaleria macrocarpa, Isotoma longiflora, and Symplocos cocchinensis. Isolation of actinomycetes was conducted using HV agar with the addition of cycloheximide, nystatin, nalidixic acid, and rifamycin. A total of 21 actinomycete isolates were obtained and tested for antimicrobial activity against Escherichia coli ATCC 25922, Staphylococcus aureus ATCC25923, Pseudomonas aeruginosa ATCC27853, and Bacillus subtilis ATCC 66923. Among the isolates, isolate KY01 was the most active to Gram-positive and Gram-negative bacteria. Morphological observation and identification using 16S rRNA gene sequence showed that the isolate KY01 was similar to Streptomyces antibioticus. An active compound from the isolate KY01 was produced using yeast peptone medium. The active compound was purified using silica-gel-column chromatography and preparative high performance liquid chromatography (HPLC). A single peak of the active compound was detected with HPLC and LCMS, which showed a retention time of 26.6 min and molecular weight (MW) 906.4474 g/mol, respectively.